Motion Detection Implementation on a Game Using Raspberry Pi - Gunawan Putra Gozali (Soegijapranata Catholic University, 2016)
Along with the development of advanced gaming technology, we can play the game with so many tools or platforms such as console games, PC games, mobile games and handheld games. The disadvantage of those games is the difficulty to connect additional sensors to the PC computer. Large power requirements will also be a constraint. Besides, the size of the PC could be a weakness that makes it difficult to carry and play anytime. Raspberry is a small computer that can be added with motion detection sensors. By using the raspberry, the researchers managed to create a game